Psikoedukasi Pemanfaatan Limbah Minyak Jelantah sebagai Produk Ramah Lingkungan - Afnita, Vinda; Manullang, Dominikus Rojoki; Hutahaean, Lidia Aprileny; Paembonan, Tiara Lestari; Dumanaw, Varisky Abraham; HS, Sahat Renol; Arsana, I Kadek Satria; Manongko, Allen A. Ch, (Universitas Negeri Padang, 2024)
Tataaran 2 area, South Tondano sub-district, Minahasa Regency, has great potential in utilizing used cooking oil waste into valuable products such as aromatherapy candle products. However, the main obstacle in maximizing this potential is the lack of local community skills in processing used cooking oil waste. In an effort to encourage economic independence based on environmental friendliness by implementing zero waste, this article will outline the methods and steps that can be used to process used cooking oil into aromatherapy candles. Training is provided through a combination of theory and direct practice, with the active participation of local communities. Evaluation results showed that the participants' skills increased significantly in processing used cooking oil into aromatherapy candles. This training was also successful increase participants' awareness of the importance of preserving nature. The results of this program show that the training is community-based can be an effective strategy to support entrepreneurial growth in society by utilizing used cooking oil waste into valuable products. The recommendation is this training program. This must be continued with training programs in selling processed products using social media